Public participation in environmental and social impact assessment for hydroelectric power projects : a case study of Bui Dam in Ghana - Atworekire, Silas (Kampala, 2016)
Unpublished dissertation (Msc. ENVT&NR) - Makerere University, 2016
Includes bibliographical references (p. 50-54)
Keywords: Water-power -- Ghana